Advances In Intelligent Food Packaging Of Meat - Koneti, Priya B; Raziuddin, M; Devangare , A A (Journal of Meat Science, 2023)
There are now numerous innovative food packaging options available on the market that let consumers monitor the items’ quality, safety, integrity, cleanliness, freshness, and purity before consumption. It’s also critical to minimise food fraud, spoilage, contamination, and ineffective food safety communication. To satisfy this need, a number of packaging technologies, including intelligent packaging and active packaging have been developed. In this article, covered a variety of intelligent packaging systems, including data carriers, indications, and sensors. By sending out visual like a change in colour, indicators provide internal visual that reveal the state of food goods. With the aid of transducers, digital sensors are able to recognise changes in the product.